Review of Stroke: The 2nd International and the 8th National Iranian Stroke Congress : Shiraz, Iran: - Borhani-Haghighi, Afshin (Galen Medical Journal, 2016)
Dear reader, Stroke is a major health problem in Iran as other developing countries. Meanwhile, epidemiological characteristics of stroke in Iranian population are different with other countries. Both population-based and hospital-based studies showed that incidence and mortality of stroke in Iran is higher than most western countries [1,2]. Higher rates of patients with young-adult stroke in Iranian population are a prominent feature too [3]. In the same time, prevalence of cerebral venous sinus thrombosis is higher than western populations [4] but the frequency of the intracranial stenosis is more or less same as Europeans [5]. The high prevalence of atherosclerotic disease in Iran can be attributed to social and economic factors, including increased life span, changes in dietary habits and an increasingly sedentary lifestyle [6]. In the light of these changes, Iranian health policymakers should consider concerted primary and secondary preventive measures to reduce the impact of this increasingly problematic public health issue. Iranians who have had a stroke consider their social, financial and rehabilitative support to be inadequate. Moreover, awareness of the manifestations of stroke is poor in the Iranian general population [7]. Consequently, the clinical status of stroke patients by the time they are transferred to the referral center may be worse than it could have been. There is an urgent need for Iranian hospitals to develop better measures to manage acute stroke patients. The second international Iranian stroke congress was held from 23-25 September 2015 in Shiraz, Iran. This Conference was a joint effort of the Clinical Neurology Research Center of Shiraz University of Medical Sciences and Iranian Stroke Association. Here we presented some selected reviews from outstanding platforms of this congress. Ghandehari presented the epidemiology of stroke in Iran [8]. Safari et al presented a comprehensive review about immunology of stroke [9]. Abolhasani-Foroughi and Nazeri summarized the role of Computed topography scan for diagnosis and treatment planning of stroke patients [10]. Lotfi discussed about pearls and pitfalls of color doppler sonography of cervical arteries [11]. We also have three reviews about clinical and radiologic aspects of cerebral venous sinus thrombosis [12-14]. Two reviews focused on importance of rehabilitation in new stroke era [15,16].